Dawn of the Dead [videorecording (DVD)] - Bates, Tyler (Universal Studios Home Video, 2004)
"When a mysterious virus turns people into mindless, flesh-eating zombies, a handful of survivors wage a desperate, last-stand battle to stay alive ... and human."--Container